The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.22547/ber/9.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Calendar Anomalies: Evidence from Pakistan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…So this also affects the movement of transactions in the capital market. This appears to amplify the calendar effect (Syed & Khan, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…So this also affects the movement of transactions in the capital market. This appears to amplify the calendar effect (Syed & Khan, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, Eid al-Fitr became an event that is likely to affect the movement of stocks in the capital market (Hinawati, 2016). Eid al-Fitr holiday that occurs is characterized by the absence of securities trading transactions in the Indonesian capital market, it will have an impact in investment decision making by investors (Syed & Khan, 2017). Capital expenditure decisions taken by investors are not only based on rational thinking, they can also be influenced by irrational factors such as psychological factors (Filipovski & Tevdovski, 2018;Syed & Khan, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of Ramadhan and Zil-Haj on the global equity indices were explored and no signi icant effects were testi ied. Likewise, Syed and Khan (2017) …”
Section: Monday Effectmentioning
confidence: 99%
“…They used firm-level data from 1993 to 2015 and found that these anomalies offer 30% to 50% annual returns in PSX. Syed and Khan (2017) studied Islamic calendar anomalies in PSX, using KSE-100 Index data over the period 1991-2014. The authors report evidence of change in volatility in some of the Islamic calendar months, however, no compelling evidence of abnormal returns associated with Islamic calendar were found.…”
Section: Overview Of Pakistani Equity Marketmentioning
confidence: 99%